EVALUASI SISTEM PROTEKSI DALAM UPAYA PENCEGAHAN BAHAYA KEBAKARAN PADA BANGUNAN GEDUNG BADAN PENANGGULANGAN BENCANA ACEH - Winardi Aramiko; Mochammad Afifuddin; Abdul Munir (Prodi Magister Teknik Sipil Unsyiah, 2021)
The Aceh Disaster Management Agency office is a government office that provides services to the community in implementing disaster management activities in a planned, integrated and comprehensive manner in the pre-disaster, emergency response and post-disaster stages. One of the important things in preventing fire hazards is an emergency response plan, namely taking the form of action in the event of a fire emergency or